1977
DOI: 10.1111/j.1600-0560.1977.tb00898.x
|View full text |Cite
|
Sign up to set email alerts
|

Granuloma Faciale

Abstract: Light and electron microscopic observations were carried out in three cases of granuloma faciale. The dense granulomatous infiltrate of the corium showed: 1) more eosinophils than suspected by light microscopy, most of them with degenerative changes; 2) Charcot-Leyden chrystals; 3) numerous large histiocytes with their cytoplasms filled with lysosomal vesicles containing various inclusions (lamellar figures, myelin bodies, circular concentric organelles, digested membrane structures). The lack of Langerhans gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0
1

Year Published

1978
1978
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 5 publications
1
2
0
1
Order By: Relevance
“…The frequent finding of vascular injury or true vasculitis and the previous reports of immunoglobulin deposits in blood vessel walls both support the concept that vasculitis/immune complex deposition is important in the pathogenesis of granuloma faciale 3,10,11 . Conversely, there have been previously reported cases of granuloma faciale in which vascular injury and immunoreactant deposition in vessel walls were absent 6,8 . Our findings of negative immunofluorescence in the blood vessel walls add support to the concept that immune complex deposition in blood vessel walls (and hence cutaneous leukocytoclastic vasculitis) may not be the primary pathogenic event in granuloma faciale.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The frequent finding of vascular injury or true vasculitis and the previous reports of immunoglobulin deposits in blood vessel walls both support the concept that vasculitis/immune complex deposition is important in the pathogenesis of granuloma faciale 3,10,11 . Conversely, there have been previously reported cases of granuloma faciale in which vascular injury and immunoreactant deposition in vessel walls were absent 6,8 . Our findings of negative immunofluorescence in the blood vessel walls add support to the concept that immune complex deposition in blood vessel walls (and hence cutaneous leukocytoclastic vasculitis) may not be the primary pathogenic event in granuloma faciale.…”
Section: Discussionsupporting
confidence: 86%
“…It has a typical histopathologic appearance consisting of an eosinophil‐rich, mixed dermal infiltrate which is separated from the epidermis and skin appendages by a thin band of uninvolved dermis and is most pronounced in perivascular areas 1–3 . Although granuloma faciale is classically considering one of the two chronic fibrosing vasculitides, along with erythema elevatum diutinum, reported vascular involvement in granuloma faciale has ranged from true vasculitis, to concentric hyalinization, to capillary dilation, to wall infiltration by inflammatory cells, to capillary proliferation, to no involvement 1,2,4–9 . Immunofluorescence findings have rarely been reported, but have included granular IgG, IgA, IgM, and C3 in the dermoepidermal junction, in blood vessel walls, and along connective tissue fibers; linear IgG only along the basement membrane zone; and IgG around blood vessels only 9–11 …”
mentioning
confidence: 99%
“…Ultrastructural analyses have shown that, because of their degranulation, the proportion of eosinophils in GF in paraffin-embedded sections can be underestimated. 9 We believe, however, that this phenomenon cannot explain the complete lack of eosinophils that is observed in some cases. We also found that extravased red blood cells were only sometimes present; pathologists should, therefore, consider a diagnosis of GF even in the absence of these features.…”
Section: Discussionmentioning
confidence: 90%
“…Das Infiltrat enthält neben Lymphozyten, Neutrophilen, Plasmazellen und Histiozyten charakteristischerweise eine unterschiedliche Zahl an eosinophilen Leukozyten [2,15,19]. Oft liegt das Infiltrat perivasal akzentuiert.…”
unclassified